The Role of Scientific Integration in Strengthening Religious Moderation on Religious Campuses in Indonesia - Alamsyah; M. Ngisomudin; Mahmudah, Siti; Susanto, Is; Alamsyah, Alamsyah; Ishomuddin, A. (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2025)
Religious moderation is an important issue in religious higher education in Indonesia, especially in State Islamic Religious Universities. In an effort to create an inclusive and tolerant academic environment, scientific integration is one of the strategic approaches. This article aims to analyze the role of scientific integration in strengthening religious moderation on religious campuses in Indonesia. This study uses a qualitative method with a case study approach. Data were collected through in-depth interviews, observations, and document analyses related to curriculum and learning guidelines at several State Islamic Religious Universities in Indonesia. The results showed that scientific integration at State Islamic Religious Universities has included aspects of religious moderation, although it is not always explicitly mentioned in the curriculum. Learning materials that combine general science and religious science facilitate the development of moderate attitudes among students. Some indicators of religious moderation found in the curriculum include respect for differences, acceptance of diversity, and strengthening the values of Pancasila as the basis of the state and a guide to life. This study also found that the Indonesian Qualifications Framework based curriculum can strengthen religious moderation if implemented systematically and comprehensively in academic activities, both through learning, research, and community service.